African peacekeepers in Mali - Peter Albrecht; Signe Marie Cold-Ravnkilde; Rikke Haugegaard (Danish Institute for International Studies (DIIS), 2017)
In 2013, the United Nations Multidimensional Integrated Stabilization Mission in Mali (MINUSMA) was established by UN Security Council Resolution 2100 to support peace-making and -building in Mali in order to prevent further destabilization of the Sahel. MINUSMA has come to represent the emerging practice of establishing UN peacekeeping missions in asymmetrical conflict environments where there is "no peace to keep." In this context, and following large-scale international interventions in Afghanistan and Iraq, European soldiers have returned to UN peacekeeping. However, African countries remain the largest troop contributors to peacekeeping missions, including MINUSMA. This new DIIS report provides new insight into the roles and experiences of African soldiers serving in MINUSMA. The report demonstrates the disproportionate dangers that confront African soldiers compared to their European and Asian counterparts in the mission. The authors argue that a number of factors shape these discrepancies, including where African soldiers are deployed in the mission area, the equipment at their disposal and how their governments support them before, during and after deployment. By October 2016, 91 of 109 MINUSMA personnel killed were from African countries located in the region around Mali, while only six were from European countries. These numbers directly affect MINUSMA's efficiency and prospects for contributing to the peace process in Mali. This report illustrates how intra-mission inequality encumbers collaboration and coordination between African and non-African units in MINUSMA. Most of the time, the units operate more or less separately, to the extent that MINUSMA risks becoming a two-tier mission. Such fragmentation, which is noticeable across all elements of the mission, must be addressed - by UN headquarters in New York and by MINUSMA itself. If these challenges are not addressed, MINUSMA as a whole will not be able to benefit from the specialized support that the European countries bring into the mission. However, the capabilities that European soldiers bring with them are indispensable if United Nations peacekeepers are to function, indeed, survive in an asymmetrical conflict environment. The report is based on a collaborative research between DIIS and the Royal Danish Defence College, RDDC.
Keywords: 300